Experimental evaluation of airborne pollutants using sensor-based monitoring - Timo Houben; Paul Remmler; Alex Romanjuta; Ema Vosgerau; Peter Dietrich; Thomas Trabert (PANGAEA, 2025)
As part of the AIAMO (Artificial Intelligence and Mobility) project funded by the BMDV, a comprehensive environmental monitoring network is currently set up in order to use this for the implementation of environmentally sensitive traffic management. To monitor air quality within the pilot region of Leipzig, air quality sensors from Robert Bosch GmbH (Bosch Air Quality Solutions, Immission Measurement Box, Model IMB 6, F041.B00.003-00) are being installed at various locations within the city. To gain a better understanding of the sensors, a test experiment was set up before they were installed in the city. In this study, the reaction of environmental sensors to following pollutants in the air is analysed under controlled conditions: NO2 (nitrogen dioxide) PM10 (particulate matter 10) PM2.5 (particulate matter 2.5) O3 (ozone) CO (carbon monoxide) The experiment was conducted on 12 August 2024 and consisted of five different test phases: Vehicle Exhaust, Cigarette Smoke, Particulate Matter, Pollen and Fossil Fuel Combustion. Each phase included specific pollutant sources, including diesel vehicles, tobacco smoke, particulate matter and simulated rain effects. The collection of real-time sensor data was complemented by controlled environmental variables such as ventilation and artificial dispersion. The results aim to improve sensor calibration, increase the accuracy of pollutant detection and provide insights into real-world environmental monitoring applications.